1984
DOI: 10.1177/0013916584164005
|View full text |Cite
|
Sign up to set email alerts
|

Any Data or None at All?

Abstract: Accuracies of self-reports of household energy consumption were examined among a sample of 2090 electricity and 1699 fuel oil and natural gas consumers. Information obtained from self-reports allowed an increase in response of 37% over what could be obtained from utility company files. Errors in measures as a result of self-reporting occurred, ranging between 10.5% and 12.6% and 24.6% and 29.3%, depending upon fuel type and respondents' use of household receipts. There was no apparent tendency toward systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…ECB and WMB were explored by means of individuals’ self-reports. Individuals’ self-reports have been widely used by many scholars in the field of environmental behaviors (Warriner et al 1984; Fujii et al 1985). By using this method, participants will be asked to indicate the frequency with which they engage in each specific type of PEBs (Gatersleben et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…ECB and WMB were explored by means of individuals’ self-reports. Individuals’ self-reports have been widely used by many scholars in the field of environmental behaviors (Warriner et al 1984; Fujii et al 1985). By using this method, participants will be asked to indicate the frequency with which they engage in each specific type of PEBs (Gatersleben et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Not only are self-reports subject to such factors as response bias and socially desirable responding, individuals' beliefs regarding ERB may demonstrate a stronger relationship with self-reports than with observed behavior (Chao & Lam, 2011;Obregón-Salido & Corral-Verdugo, 1997). However, self-reports and observational data have been found to be significantly correlated for recycling and reuse (Corral-Verdugo, 1997;Gamba & Oskamp, 1994) and energy use (Chao & Lam, 2011;Warriner, McDougall, & Claxton, 1984).…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, the executives who filled out the survey had little reason to present a more favorable picture of themselves than they knew was the case. Several studies show that self-reported behavior and actual behavior are strongly correlated (Warriner et al, 1984;Fuj et al, 1985;Bernard, 2000;Gatersleben et al, 2002). A final reason to expect that a potential socially-desirability response bias will not blur the analysis is that we found a high variance in the scores of the various components of CSR.…”
Section: Data Collection and Reliabilitymentioning
confidence: 63%